1997
DOI: 10.1021/je960294x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Solvation of Some Copper(II) Salts in Water + N-Methyl-2-pyrrolidinone Solvent Mixtures at 30 °C

Abstract: The preferential solvation of copper(II) iodate, benzoate, formate, salicylate, p-methylbenzoate, and p-nitrobenzoate has been studied in water + N-methyl-2-pyrrolidinone mixtures at 30 °C by Gibbs energies of transfer and solvent transport number measurements. The Gibbs transfer energies of the salts were split into their ionic values using the transfer energies of copper ion determined on the basis of the negligible liquid junction potential method. These results were also compared with those obtained on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Therefore, the patches of passivation film will contribute to the local galvanic corrosion, thus pitting will happen. Thirdly, it is reported that the copper iodate and copper periodate have a high solubility product and this could enhance the CMP MRR [28,35,51]. Therefore, the comparatively high solubility of the surface products could also enhance the static chemical corrosion in acidic solutions.…”
Section: Corrosion Behavior Of Copper In Periodate-based Solutionmentioning
confidence: 99%
“…Therefore, the patches of passivation film will contribute to the local galvanic corrosion, thus pitting will happen. Thirdly, it is reported that the copper iodate and copper periodate have a high solubility product and this could enhance the CMP MRR [28,35,51]. Therefore, the comparatively high solubility of the surface products could also enhance the static chemical corrosion in acidic solutions.…”
Section: Corrosion Behavior Of Copper In Periodate-based Solutionmentioning
confidence: 99%
“…29 Moreover, both Cu (IO 4 ) 2 and Cu (IO 3 ) 2 are more soluble than cpper oxides. 29,41,42 Therefore, it is probable that, with the enhancement of the concentration of KIO 4 , the further growth of copper RR is resulted from the augment of the proportion of Cu(IO 4 ) 2 and Cu(IO 3 ) 2 in the passivating film. Ruthenium and its oxides convert into soluble RuO 4 2− species by reactions 8 to 10.…”
Section: • [ ]mentioning
confidence: 99%